Health Provider Payment Reforms in China : What International Experience Tells Us - World Bank (Washington, DC, 2017)
This paper examines health provider payment reforms in China the present system and how it evolved, and changes that will improve it in the context of ongoing health reform. The paper begins with a brief introduction and background discussion followed by two substantive sections experiments with case-based payment systems, and experiments with alternative government budget payment methods. This is followed by an examination of what has worked in China and elsewhere. The concluding discussion considers lessons for China and next steps. Many policy instruments and reforms have been implemented to use National Cooperative Medical System (NCMS), Basic Medical Insurance (BMI), and government health budgets more efficiently. These include alternative payment systems, reduced drug prices, essential drug lists, controlled use of high technologies, and strengthening the primary healthcare system.